Integral Algorithms to Evaluate TiO[sub.2] and N-TiO[sub.2] Thin Films’ Cytocompatibility - Zhuravleva, Irina Yu; Surovtseva, Maria A; Alshevskaya, Alina A; Surovtsev, Nikolay V; Okotrub, Konstantin A; Kim, Irina I; Nasimov, Dmitriy A; Bondarenko, Natalia A; Kuzmin, Oleg S; Poveshchenko, Olga V (International journal of molecular sciences, 2022)
Titanium oxide (TiO[sub.2]) and oxynitride (N-TiO[sub.2]) coatings can increase nitinol stents’ cytocompatibility with endothelial cells. Methods of TiO[sub.2] and N-TiO[sub.2] sputtering and cytocompatibility assessments vary significantly among different research groups, making it difficult to compare results. The aim of this work was to develop an integral cytocompatibility index (ICI) and a decision tree algorithm (DTA) using the “EA.hy926 cell/TiO[sub.2] or N-TiO[sub.2] coating” model and to determine the optimal cytocompatible coating. Magnetron sputtering was performed in a reaction gas medium with various N[sub.2]:O[sub.2] ratios and bias voltages. The samples’ morphology was studied by scanning electron microscopy (SEM) and Raman spectroscopy. The cytocompatibility of the coatings was evaluated in terms of their cytotoxicity, adhesion, viability, and NO production. The ICI and DTA were developed to assess the cytocompatibility of the samples. Both algorithms demonstrated the best cytocompatibility for the sample sputtered at U[sub.bias] = 0 V and a gas ratio of N[sub.2]:O[sub.2] = 2:1, in which the rutile phase dominated. The DTA provided more detailed information about the cytocompatibility, which depended on the sputtering mode, surface morphology, and crystalline phase. The proposed mathematical models relate the cytocompatibility and the studied physical characteristics.